Behavioral and Physiological Evidence for Palp Detection of the Male-Specific Attractant Cuelure in the Queensland Fruit Fly (Bactrocera tryoni) - Verschut, Thomas A.; Farnier, Kevin; Cunningham, J. Paul; Carlsson, Mikael A. (Frontiers in Physiology, 2018)
The Queensland Fruit fly, Bactrocera tryoni, has received much attention as one of the worst horticultural pests in Australia attacking a large variety of fruit crops. To defeat pest insects, olfactory attractants have been developed and widely used in lure and kill strategies. Male B. tryoni are strongly attracted to the compound raspberry ketone and its synthetic analogue, cuelure. Despite the strong behavioural response, a recent study failed to show any activation of antennal receptors to cuelure. Therefore, we hypothesised that cuelure may be detected by an accessory olfactory organ, the maxillary palp. Combining behavioural and physiological experiments we clearly demonstrate that male flies, but not female flies, primarily use the maxillary palps and not the antennae to detect and respond to cuelure. Furthermore, regardless of satiety status, male flies always preferred cuelure over a sugar rich source, unless the maxillary palps were excised.